PENGARUH IMPLEMENTASI WORDWALL QUIZ TERHADAP HASIL BELAJAR SISWA DALAM MATA PELAJARAN BAHASA INDONESIA - Viola, Maria Felicita; Sarifah, Iva; Yudha, Chrisnaji Banindra (Universitas Negeri Medan, 2024)
This research uses a quasi-experimental method with a one group pretest-posttest design to measure the influence of the interactive media Wordwall Quiz on students' Indonesian language learning outcomes. The research was conducted with a sample of 20 class V students at SD Mekarsari. Data were analyzed using normality tests and hypothesis testing with the help of SPSS 29 for Windows. The research hypothesis is that there is a change in the value of the Indonesian language after using interactive media based on Wordwall Quiz. The research results showed that there was a significant increase in post-test scores compared to the pre-test in Indonesian language subjects after using the Wordwall Quiz learning media. The average student pre-test score was 55.50, while the average post-test score reached 81.60. These results indicate that the use of interactive media Wordwall Quiz is effective in improving student learning outcomes. The statistical test using the paired sample test shows a t value of -6.772 with a significance level of 0.001, which shows that there is a significant difference between the pre-test and post-test results. Based on these results, it can be concluded that the interactive media Wordwall Quiz can have a positive and significant influence on student learning outcomes.